Compensatory and Catalyzing Beliefs: Their Relationship to Pro-environmental Behavior and Behavioral Spillover in Seven Countries - Capstick, Stuart; Whitmarsh, Lorraine; Nash, Nick; Haggar, Paul; Lord, Josh (Frontiers in Psychology, 2019)
There has been growing research interest in behavioural spillover and its potential for promoting more widespread lifestyle change than has typically been achieved through discrete behavioural interventions. There are some routes by which spillover could take place without conscious attention or explicit recognition of the connections between separate behaviours. However, in many cases it can be expected that the making by an individual of a conceptual association between behaviours, specifically in terms of their compensatory (suppressing further action) or catalysing (promoting further action) properties, is a prerequisite for both negative and positive spillover. Despite this, relatively little research has been carried out to assess the beliefs about spillover processes that may be held by individuals themselves, nor to measure these directly. We develop and evaluate a survey-based instrument for this purpose, doing so in a sample of seven countries worldwide: Brazil, China, Denmark, India, Poland, South Africa, and the UK (approx. 1,000 respondents per country). Our approach allows us to assess the psychometric properties of the spillover measures and to examine their cross-cultural properties, including the relationship between beliefs about behavioural spillover and other key variables such as pro-environmental identity and personal values. We observe higher levels of endorsement of compensatory beliefs than previous research, and even higher levels of endorsement of novel items assessing catalysing beliefs. For the first time, we present evidence of the validity of such measures with respect to comparable constructs, and in relation to people’s consistency across different types of behaviours. We reflect on the implications of considering spillover in the context of people’s subjective beliefs, and offer recommendations for developing this line of research in the broader context of spillover research and within a cross-cultural framework.